تطور الذكاء الأخلاقي لدى الأطفال بعمر 5-6-7 سنة - الخفاف، إيمان علي عباس (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاجتماعية والانسانية, 2017)
يستهدف البحث الحالي التعرف على تطور مستوى الذكاء الأخلاقي لدى الأطفال والكشف عن دلالة الفروق في مستوى الذكاء الأخلاقي كل ذلك بحسب متغيري: العمر (5-6-7) سنة والجنس (ذكور إناث). تكونت عينة البحث من الأطفال بعمر (5-6-7) سنوات في رياض الأطفال والمدارس الابتدائية)، للعام الدراسي 2012/2011، ولتحقيق هدف البحث تم اعتماد مقياس الذكاء الأخلاقي المعد من قبل (الخفاف والحيالي، 2012) للبيئة العراقية للأطفال بأعمار ست سنوات، المتضمن (33) فقرة، موزع على (7) مجالات، ولتحليل النتائج إحصائيا تم استخدام معامل ارتباط (بيرسون)، الاختبار التائي T-test لعينتين مستقلتين، والاختبار التائي لعينة واحدة، وتحليل التباين الثنائي، وتوصلت الدراسة إلى النتائج الآتية: -إن الفرق في درجات الذكاء الأخلاقي وحسب متغير العمر كان ذو دلالة إحصائية. -اتخذ المسار التطوري لمفهوم الذكاء الأخلاقي نمطاً مستمرا.
The current research aims to identify: The level of moral development of intelligence in children, according to two variables: Age (5-6-7) years, sex (male-female); Significance of differences in the level of moral intelligence, according to two variables: Age (5-6-7) years, sex (male-female). The sample search of children aged (5-6-7) years in kindergartens and primary schools), for the academic year 2011/2012, and to achieve the aim of the research was to adopt the moral intelligence prepared a scale of before Al-kafaf and Hayali (2012) for the Iraqi environment for children ages six years , containing 33 paragraphs, distributor (7) areas, and to analyze the results statistically been using Pearson correlation coefficient, Altaia t-test test for two independent samples, (t-test) for one sample, and two-way analysis of variance, the study found the following results: -The difference in the degree of moral intelligence and by age variable was statistically. Significant. - Has taken the evolutionary path of the concept of moral intelligence pattern continues.
Keywords: علم النفس التربوي -- رياض الأطفال -- سيكولوجية النمو -- الذكاء الأخلاقي